2023
DOI: 10.1177/23779608231207274
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Stress and Coping Behaviors among Nursing Students Throughout Their First Clinical Training

Dalia Toqan,
Ahmad Ayed,
Malakeh Z. Malak
et al.

Abstract: Introduction Clinical training allows nursing students to acquire and strengthen their psychomotor abilities, which is an important component of nursing education. The clinical components of nursing training programs were much more demanding than the academic ones. Purposes The purpose of this study was to examine sources of stress-related and coping behaviors during first clinical training among nursing students in the Arab American University. Methods The study was cross-sectional and conducted with a conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Students may be able to benefit from this coping strategy through activities that facilitate proper physiological functioning such as eating healthy foods and instituting adequate rest and sleep patterns. Similar results were observed in the study of Toqan et al (2023), that revealed a combination of problemsolving and avoidance, both of which are interpersonal, as well as optimism which is an intrapersonal coping strategy were occasionally utilized by students to manage stressors. While transference behaviors like feasting a deep sleep, relaxing by watching TV, taking a shower, exercise, etc.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Students may be able to benefit from this coping strategy through activities that facilitate proper physiological functioning such as eating healthy foods and instituting adequate rest and sleep patterns. Similar results were observed in the study of Toqan et al (2023), that revealed a combination of problemsolving and avoidance, both of which are interpersonal, as well as optimism which is an intrapersonal coping strategy were occasionally utilized by students to manage stressors. While transference behaviors like feasting a deep sleep, relaxing by watching TV, taking a shower, exercise, etc.…”
Section: Discussionsupporting
confidence: 85%
“…Similar findings of Shdaifat et al (2018) point out that nursing students experience a moderate level of stress because of their teacher and nursing staff, peers, daily life, and taking care of patients. Moreover, a study in the Arab American University yielded the same results that identify teachers and nursing staff as the main stressors of nursing students in their first clinical training (Toqan et al, 2023). A phenomenological study among Malawian nursing students revealed that a lecturer who interacts in a "policing manner" induces more stress (Msiska et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Numerous studies have revealed that the last year of university and the time preceding clinical practice make healthcare students more apprehensive ( Ahorsu et al, 2021 ; Pramukti et al, 2020 ; Toqan et al, 2023 ). Many students find that going to class at school helps them manage and maintain social connections.…”
Section: Literature Reviewmentioning
confidence: 99%